Faktor-Faktor Yang Memprediksi Purchase Intention Skin Care Garnier Di Indonesia - Clara Tanuwijaya; Frangky Slamet (Jurnal Manajerial Dan Kewirausahaan, 2021)
Brand awareness is the consumer's ability to remember a brand, brand association is a positive / negative perception when remembering a brand, perceived quality is a customer evaluation of brand superiority, brand loyalty is a customer commitment to a brand, and purchase intention is an evaluation of consumers to decide to buy a product. This study aims to determine the predictions of brand awareness, brand association, perceived quality and brand loyalty to purchase intention with a conclusive quantitative method and a cross-section study. Data obtained by means of a survey made with "google form" sent via e-mail and WhatsApp to 100 respondents who are people who have used the Garnier brand skin care for at least 3 years in Indonesia with a non-probability sampling method (purposive sampling). Then there are 4 hypotheses in this study which were analyzed using PLS-SEM with SmartPLS 3. The results of this study indicate that brand awareness, brand association, perceived quality and brand loyalty each predict positively the purchase intention of Garnier brand skin care users in Indonesia. Brand awareness merupakan kemampuan konsumen untuk mengingat merek, brand association merupakan persepsi positif/negatif ketika mengingat merek, perceived quality merupakan evaluasi pelanggan pada keunggulan merek, brand loyalty komitmen pelanggan pada merek, dan purchase intention merupakan evaluasi konsumen untuk memutuskan beli produk. Penelitian ini bertujuan untuk mengetahui prediksi brand awareness, brand association, perceived quality dan brand loyalty terhadap purchase intention dengan metode kuantitatif berjenis konklusif dan cross-sectiona study. Data diperoleh dengan cara survei yang dibuat dengan “google form” yang dikirimkan melalui email dan whatsapp terhadap 100 responden yang merupakan orang yang menggunakan skin care merek Garnier minimal 3 tahun di Indonesia dengan metode non-probability sampling (purposive sampling). Kemudian terdapat 4 hipotesis pada penelitian ini yang dianalisis menggunakan PLS-SEM dengan SmartPLS 3. Hasil penelitian ini menunjukkan bahwa brand awareness, brand association, perceived quality dan brand loyalty masing-masing memprediksi positif purchase intention pengguna skin care merek Garnier di Indonesia.